Disaster management: emergency nursing and medical personnel’s knowledge, attitude and practices of the East Coast region hospitals of Malaysia - Ahayalimudin, Nurul'Ain; Osman, Nor Naimah Saidah (2016)
tBackground: Disaster management is critical, as its insight could diminish the impact of a disaster, and par-ticipation of emergency medical personnel is crucial. This study explores emergency medical personnel’sknowledge, attitude and practice towards disaster management.Methodology: This study utilised a cross-sectional study design, and the data collected from 194 emer-gency nursing and medical personnel (staff nurses, doctors and assistant medical officers), using aquestionnaire.Results: Majority of the personnel had an adequate knowledge and practices, and portrayed a posi-tive attitude towards disaster management. Amongst the sociodemographic factors studied, gender andeducation level were significantly associated with increased knowledge and practice scores. Workingexperience, involvement in disaster response and attended disaster training had a significant associa-tion with higher practice scores. None of the sociodemographic factors studied had an effect on attitudescores.Conclusion: Despite the diversity of their backgrounds, respondents exhibited their adequate knowledgeand practice, and had positive attitudes towards disaster management. It is substantial for emergencynursing and medical personnel, to inhibit the severity of the impacts of the disasters. Their knowledge,attitude and practice studies could assist in the implementation of programmes relevant to disastermanagement to ensure their preparedness to assist the affected communities.